Ginkgo biloba extract-761 protects myocardium by regulating Akt/Nrf2 signal pathway - Chen X; Ren S; Dong J; Qiu C; Chen Y; Tao H (Dove Medical Press, 2019)
Xiao-jie Chen,1 Shu-min Ren,2 Jian-zeng Dong,1 Chun-guang Qiu,1 Ying-wei Chen,1 Hai-long Tao1 1Department of Cardiology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China; 2Department of Genetics and Prenatal Diagnosis, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, China Objective: The aim of this study was to investigate the protective effect and mechanism of Ginkgo biloba extract-761 (EGb 761) in the rat with myocardial ischemia–reperfusion injury (MIRI).Materials and methods: Forty Sprague Dawley rats were randomly divided into following four groups: sham group, I/R group and EGb 761 groups (20 and 40 mg/kg). MIRI model was established after 14 days of administration. The myocardial infarct size and myocardial histology were measured and compared. Meanwhile, the levels of creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), troponin T (TnT), TNF-α, IL-6, IL-1β, superoxide dismutase (SOD), malondialdehyde (MDA) and glutathione peroxidase (GSH-Px) were evaluated. Western blot was used to detect the expression of Caspase-3, Bax, Bcl-2, HO-1, Nrf2, Akt, p-Akt and nuclear protein Nrf2.Results: The levels of infarct size, CK-MB, LDH, TnT, TNF-α, IL-6 and IL-1β in the EGb 761 groups were significantly lower than those in the ischemia/reperfusion (I/R) group. The content of MDA was lower in the myocardium, whereas the activities of SOD and GSH-Px were higher than those in the I/R group. The expressions of Caspase-3 and Bax in the EGb 761 groups were significantly lower than those in the I/R group, whereas the expressions of Bcl-2, p-Akt and HO-1 and nuclear protein Nrf2 in the EGb 761 groups were higher than those in the I/R group.Conclusion: EGb 761 might inhibit the apoptosis of myocardial cells and protect the myocardium by activating the Akt/Nrf2 pathway, increasing the expression of HO-1, decreasing oxidative stress and repressing inflammatory reaction. Keywords: Ginkgo biloba extract, myocardial ischemia-reperfusion injury, oxidative stress, superoxide dismutase